2021
DOI: 10.3389/fspor.2021.653962
|View full text |Cite
|
Sign up to set email alerts
|

Increased Leg Strength After Concurrent Aerobic and Resistance Exercise Training in Older Adults Is Augmented by a Whole Food-Based High Protein Diet Intervention

Abstract: Most studies in older adults have utilized powdered protein supplements or oral nutrition solutions as a source of additional dietary protein, but whole foods may provide a greater anabolic stimulus than protein isolated from food matrices. Therefore, the present study investigated a concurrent aerobic and resistance exercise training program in older adults, in the absence or presence of a high protein whole food-based dietary intervention, for effects on strength, physical function, and body composition. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 54 publications
3
7
0
1
Order By: Relevance
“…Meta-analyses analyzing RCTs conducted with elderly subjects also have shown that protein supplementation alone is ineffective and that protein supplementation combined with resistance training is more effective in enhancing muscle mass and strength [ 10 , 22 , 31 , 32 ]. In the combined exercise and high protein whole food-based diet intervention, dietary intervention enhanced the training-induced improvements in lower limb strength of older adults, compared to an exercise or diet only intervention [ 33 ], which also supports the findings of this study.…”
Section: Discussionsupporting
confidence: 85%
“…Meta-analyses analyzing RCTs conducted with elderly subjects also have shown that protein supplementation alone is ineffective and that protein supplementation combined with resistance training is more effective in enhancing muscle mass and strength [ 10 , 22 , 31 , 32 ]. In the combined exercise and high protein whole food-based diet intervention, dietary intervention enhanced the training-induced improvements in lower limb strength of older adults, compared to an exercise or diet only intervention [ 33 ], which also supports the findings of this study.…”
Section: Discussionsupporting
confidence: 85%
“…Of interest, a ‘whole-food protein approach’ was used to increase protein intake in the protein+exercise and the protein-only group from ∼1.0 to ∼1.5 g/kg body mass per day. The combined protein+exercise intervention resulted in a statistically larger improvement in lower extremity strength when compared with the exercise-only group, as well as a larger improvement in appendicular lean mass, although the latter finding did not reach statistical significance [16 ▪▪ ]. As noted by the authors, the benefits may be explained by the large increase in protein intake reached through their whole-food approach, adding an extra 40–55 g protein on a daily basis.…”
Section: Exercise Training and Supplementation Of Protein Amino Acids...mentioning
confidence: 81%
“…Finally, a recent study that did show an added benefit of protein supplementation on top of a moderate-intensity to high-intensity exercise program was performed by Timmons et al [16 ▪▪ ]. In their study, 56 healthy older men and women performed 12 weeks of supervised, high-intensity concurrent exercise known to improve muscle strength, physical function, and body composition.…”
Section: Exercise Training and Supplementation Of Protein Amino Acids...mentioning
confidence: 99%
“…Nuestros resultados están acordes con estudios previos donde la intervención nutricional se establece como un componente importante cuando la actividad física o el ejercicio forman parte de la intervención para generar cambios en la composición corporal. Esta función permite aumentar los beneficios de los resultados del programa de formación en diferentes factores (Timmons et al, 2021). Sin embargo, no toda la evidencia respalda la importancia de asesorar sobre nutrición en combinación con un programa de entrenamiento cuando se midieron los beneficios relacionados con la salud, los cambios en la composición corporal y las adaptaciones al entrenamiento en mujeres sanas (Kyröläinen et al, 2018).…”
Section: Discussionunclassified